The Functional Relationship Between The Constitutional State and the Aims of Education in the Digital Society - GuimarÃ£es, Diego Fernandes; de Araújo Borges, María Creusa (Ius Humani. Jornal do direito, 2025)
The aim of this article is to analyses the functional relationship between the purposes of education and the constitutional state in an increasingly digitalized society. Empirical data reveals the social restructuring promoted by the growing use of digital technologies which, in addition to promoting changes in cultural patterns, has infected the basis of the constitutional state, in particular the overestimation of pluralism and human dignity as an anthropological-cultural fundament. However, given the functional relationship between the aims of education and the constitutional state, in the case of Brazil, the 1988 Federal Constitution contains the antidotes to these pathologies, which consist of the normative framework provided by the aims of education set out in art. 205, which are opened to continuous recontextualization, including in a less analogue and more digital scenario.